Depletion‐Resistant CD4 T Cells Enhance Thymopoiesis During Lymphopenia. Issue 8 (17th May 2017) - Ayasoufi, K.; Fan, R.; Valujskikh, A.
Abstract : Lymphoablation is routinely used in transplantation, and its success is defined by the balance of pathogenic versus protective T cells within reconstituted repertoire. While homeostatic proliferation and thymopoiesis may both cause T cell recovery during lymphopenia, the relative contributions of these mechanisms remain unclear. The goal of this study was to investigate the role of the thymus during T cell reconstitution in adult allograft recipients subjected to lymphoablative induction therapy. Compared with euthymic mice, thymectomized heart allograft recipients demonstrated severely impaired CD4 and CD8 T cell recovery and prolonged heart allograft survival after lymphoablation with murine anti‐thymocyte globulin (mATG). The injection with agonistic anti‐CD40 mAb or thymus transplantation only partially restored T cell reconstitution in mATG‐treated thymectomized mice. After mATG depletion, residual CD4 T cells migrated into the thymus and enhanced thymopoiesis. Conversely, depletion of CD4 T cells before lymphoablation inhibited thymopoiesis at the stage of CD4 − CD8 − CD44 hi CD25 + immature thymocytes. This is the first demonstration that the thymus and peripheral CD4 T cells cooperate to ensure optimal T cell reconstitution after lymphoablation. Targeting thymopoiesis through manipulating functions of depletion‐resistant helper T cells may thus improve therapeutic benefits and minimize the risks of lymphoablation in clinical settings. Abstract : This study demonstrates that depletion‐resistant memory CD4 T cells migrate into the thymus and facilitate thymopoiesis following antibody‐mediated lymphoablation. Snyder and Farber's editorial is onpage 1970 .